Variables asociadas a enfermedad diarreica en lactantes mayores atendidos en un establecimiento de Salud I-3 Iquitos, 2023 - Paredes Flores, Margarita (2024)
The general objective of this research study was to determine the relationship between personal variables (age, sex, personal hygiene, breastfeeding, complementary feeding, vaccination), environmental variables (water consumption, solid waste management, excreta disposal, overcrowding) with diarrheal disease in older infants, cared for in a Health I – 3 Iquitos, 2023 establishment; It was a descriptive, correlational study, non-experimental design, we worked with a sample of 148 older infants, the technique was the interview and the instrument was a data collection sheet. To test the hypothesis, chi2 was used with a significance level α ≤ 0.05. The results were: there is a significant statistical relationship between vaccination (p=0.005), water consumption (p=0.001) and overcrowding (p=0.048) with diarrheal disease in older infants; There was no statistically significant relationship between age (p= 0.243), sex (p= 0.642), hygiene (p= 0.292), breastfeeding (p= 0.251), complementary feeding (p= 0.853) and solid waste management (p= 0.390). and elimination of excreta (p= 0.865), Concluding: that personal variable such as vaccination and environmental variable such as water consumption and overcrowding are variables associated with diarrheal disease in older infants, cared for in a Health facility I – 3 Iquitos, 2023 and the personal variables age, sex, breastfeeding hygiene, complementary feeding; Environmental variables such as solid waste management and excreta disposal were not associated.